2018
DOI: 10.1111/lang.12313
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Learning and Long‐Term Retention of New Word Meanings From Stories: The Effect of Number of Exposures

Abstract: This study used a Web‐based naturalistic story‐reading paradigm to investigate the impact of number of exposures on incidental acquisition and long‐term retention of new meanings for known words by native English‐speaking adults. Participants read one of four custom written stories in which they encountered novel meanings (e.g., a safe concealed within a piece of furniture) for familiar words (foam). These meanings appeared two, four, six, or eight times in the narrative. Results showed reasonably good memory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
106
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(120 citation statements)
references
References 39 publications
11
106
3
Order By: Relevance
“…Following this reasoning, several studies have shown that it is possible to learn vocabulary implicitly through reading in our foreign language 3 – 7 . In addition, we know that people incorporate new lexical forms with as little as one exposure in their native language and as little as two exposures in their foreign language 4 , but that learning improves with exposure to multiple instances of the word 8 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Following this reasoning, several studies have shown that it is possible to learn vocabulary implicitly through reading in our foreign language 3 – 7 . In addition, we know that people incorporate new lexical forms with as little as one exposure in their native language and as little as two exposures in their foreign language 4 , but that learning improves with exposure to multiple instances of the word 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This is in part because these skills seem to be affected by knowledge of the language and experience in that particular task 9 , 10 . Although the number of times people encounter a word affects how well they learn and remember it 5 , 8 , there is not much literature on how spreading these encounters across passages affects learning. One of the ways in which this spread is quantified is through contextual diversity—namely, the number of texts in which a word appears in a database 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The speed with which dominant and subordinate meanings are accessed can be affected by learning, prior knowledge, and experience [4][5][6][7][8][9][10][11][12][13][14]. With respect to learning and experience, Hulme et al [9] showed that adults are able to acquire new meanings for previously non-ambiguous words. Participants were exposed to these novel meanings within a story narrative, and their accuracy in recalling the novel meanings increased with the number of times they encountered the meaning in the story narrative.…”
Section: Introductionmentioning
confidence: 99%